Activity for mental health - Bowins, Brad (United Kingdom: Academic Press, 2020)
'Activity For Mental Health explores all activities, including physical, social, natural, cognitive, art/hobby and music as a means to both preventing and treating mental illness. This book not only reviews evidence-based research behind activity, but also explores how these forms of activity can treat mental illnesses. First, the reader is introduced to the concepts of Formal Behavioral Activation Therapy (BAT) and informal activity as an effective treatment option. Case examples aid in connecting the benefits to real life scenarios. Following the introduction, each activity is introduced in separate chapters, including physical, social, natural, cognitive, art/hobby and music. This book will provide researchers and clinicians the information needed to help customize treatment options for their patients suffering from mental illness'--
Keywords: Mental health; Mental illness; Defense mechanisms (Psychology); Mental illness -- Diagnosis